(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Gesture-controlled interfaces are revolutionizing the way humans interact with computers and smart devices by replacing traditional input methods with intuitive body movements. These systems leverage advanced technologies such as computer vision, depth sensing, machine learning, and wearable sensors to accurately interpret user gestures in real time. This survey paper presents a comprehensive exploration of gesture-based interaction systems, beginning with a discussion of the core technologies that enable gesture recognition and tracking. It then delves into various application domains, including gaming, healthcare, robotics, virtual and augmented reality, and smart home environments, highlighting how gesture control enhances usability and user experience in each context. The paper also addresses the major challenges faced in this field, such as gesture ambiguity, environmental sensitivity, computational complexity, and user diversity. Finally, it outlines the latest trends and future research directions, including the integration of AI, multimodal interfaces, and the development of more robust, context-aware systems. By offering an in-depth overview, this survey aims to guide researchers, developers, and industry professionals in understanding current advancements and identifying opportunities for innovation in gesture-based human-computer interaction.